CORPORATE SOCIAL RESPONSIBILITY, INNOVATION AND EMPLOYEES ENGAGEMENT - THE CASE OF MOROCCAN COMPANIES - Houda Jorio; Kasmi Samira; Mustapha Machrafi (Journal of Economic and Social Development (Varaždin), 2021)
The aim of this paper is to examine the most effective role that companies may play in the rehabilitation of the city of Salé. In fact, in order for a city to be developed, companies need to consider a variety of strategies in order to be innovative within their work activities. By integrating corporate social programs as a part of their mission, value, and culture, companies not only motivate employees but also make them innovative in their work performance, allowing them to boost their innovative skills and in return, benefit their community, companies, and their city. Our study supports the affirmation that the sense of belonging along with a strong corporate social responsibility measures have all proven to contribute positively to a city’s development.